2016
DOI: 10.1093/ee/nvw109
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Latitude, Nematode Parasitization, and FemaleSirex nigricornis(Hymenoptera: Siricidae) Fitness

Abstract: Sirex nigricornis F. (Hymenoptera: Siricidae) is an innocuous pine-inhabiting woodwasp native to eastern North America, utilizing dead or dying pine trees as hosts. Although S. nigricornis F. does not cause economic damage, a closely related species, Sirex noctilio, was discovered in New York in 2004 and has continually spread throughout the northeastern United States and southern Canada, threatening the multi-billion-dollar pine timber industry of the southeastern United States and raising interest about pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
2
6
1
Order By: Relevance
“…We found that parasitized S. nigricornis females had on average 21% fewer eggs than unparasitized females, a general trend also reported by Hartshorn, Chase, et al (2016). Among the parasitized females, an average of 79% of their eggs contained nematodes.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We found that parasitized S. nigricornis females had on average 21% fewer eggs than unparasitized females, a general trend also reported by Hartshorn, Chase, et al (2016). Among the parasitized females, an average of 79% of their eggs contained nematodes.…”
Section: Discussionsupporting
confidence: 89%
“…This rate of sterilization may assist in retention of the nematodes in a host population; none of the locations we studied averaged 0 or 100% egg sterilization, which has been found in other associations (Table 1). Prevalence of nematode parasitism in S. nigricornis populations differed by site, agreeing with Hartshorn, Chase, et al (2016) that Arkansas had high prevalence; however, this level was nowhere near the high prevalences reported for S. noctilio in Australia (Bedding & Akhurst, 1974). Deladenus proximus had a positively density dependent relation to the host within trees and parasitized more males than females.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations